Advertising and reality : a global study of representation and content - Hetsroni, Amir. (New York : Continuum International Publishing Group, 2012)
'An extensive study of the ways in which we are represented in advertising. Leading scholars from different countries, who specialise in marketing communication and media studies, review and analyse different forms of advertising and give a truly cross-cultural view of the issues at hand. This edited collection contains a wide-ranging discussion of advertising's relationship to sexuality, violence, family activities, gender roles, vocations, minorities' roles, periodical reconstruction and more.' --From back cover.
Includes bibliographical references and index.
Keywords: Advertising -- Moral and ethical aspects; Advertising -- Psychological aspects; Advertising -- Religious aspects; Sex in advertising; Older people in advertising; Mass media -- Social aspects